Drivers of Corporate Social Responsibility in the Competitive Era - Rajlaxmi Srivastava , Rajni Rastogi, Namrata Singh, (International Journal of Scientific Research and Management (IJSRM), 2017)
In the time of commercialization and industrialization all the companies are trying to gain more and more profits but along withthis a new practice derived in the recent years i.e. Corporate Social Responsibility which means “A continuing commitment by business tobehave ethically and contribute to economic development while improving the quality of life of the workforce and their families as well as ofthe local community and society at large”. The concept of CSR started very slowly in India .At present the companies and the business menare realizing the importance of CSR not only for earning the profit but also for the society. This paper focusing on the various driverswhich are pushing business towards the CSR like shrinking role of Government, Demands for greater disclosure, increased customerinterest etc. The study also includes the importance of CSR for the general public, for the companies and very important towards theenvironment